Fast full-wave calculation of electromagnetic fields based on weak-form volume integral equation for MRI applications - Huang, Shao Ying; Ma, Zu-Hui; Wan, Luo; Yu, Wenwei; Vaughan, J. Thomas (Journal of engineering (Stevenage, England), 2018)
High-field magnetic resonance imaging (MRI) scans have safety problems because energy is not homogeneously distributed in the human body. A prescan where energy and temperature distributions are calculated for input energy budgeting can significantly lower the risk. Therefore, fast and accurate calculations of the electromagnetic (EM) fields of an MRI system with a subject under scan are needed. Here, the authors present a fast EM solver based on a weak-form volume integral equation (VIE) for solving this problem. The proposed approach calculates the EM field inside the human body at a high speed without sacrificing accuracy. In the proposed approach, the VIE formulation for an inhomogeneous dielectric object is employed for near-field calculations. The operation on a dense matrix resulted by the VIE is accelerated by fast Fourier transform (FFT) in conjunction with the latest efficient iterative method. Numerical experiments are presented to show the speed and accuracy of the proposed EM solver.